2020
DOI: 10.1021/acs.jpcc.0c05766
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Small-Angle Neutron Scattering Analysis of the Initial Deuteride Formation of Deuterium–Cerium Reactions under a Controlled Gas Flow

Abstract: Metrics & MoreArticle RecommendationsABSTRACT: "Real-life" metals inevitably form the oxide layer, thus leading to complex initial hydriding processes, which are still unclear because of the experimental challenges in monitoring elemental steps including surface sorption, permeation, and concentration of hydrogen. In this study, the deuteride precipitation caused by the concentration of deuterium was successfully measured by the in situ small-angle neutron scattering (SANS) method, which used a selfdesigned re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…(a) A schematic diagram of the in situ SANS experiment of the deuterium-cerium reaction. Reproduced with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Other Neutron Scattering Techniques For Catalysis Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…(a) A schematic diagram of the in situ SANS experiment of the deuterium-cerium reaction. Reproduced with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Other Neutron Scattering Techniques For Catalysis Researchmentioning
confidence: 99%
“…With the development of in situ setups, in situ SANS has been used to investigate several different systems, as demonstrated in Figure . By using in situ SANS and a custom reaction chamber (Figure a), Yan et al studied deuteride formation on the surface of cerium (coated with a surface oxide layer). , It was found that deuterides were formed as soon as deuterium was absorbed on the sample with a thin oxide layer, while for the sample with a thick oxide layer, the precipitation of deuterides was delayed . Prabhu et al developed an in situ electrochemical SANS methodology, which enabled direct measurements of nanomaterial dispersion structure under redox reactions at the vitreous carbon electrode (Figure b). , A feasibility test was performed on ZnO nanoparticles in 50 mmol/L NaCl deuterium oxide solution under bulk electrolysis at negative potentials. , The in situ SANS results showed irreversible nanoparticle structural changes during the potential cycle. , To follow the structural changes under continuous chemical reactions, Hayward et al proposed to use the setup shown in Figure c for SANS experiments .…”
Section: Other Neutron Scattering Techniques For Catalysis Researchmentioning
confidence: 99%
See 2 more Smart Citations